Association between circulating tumor necrosis factor-related biomarkers and estimated glomerular filtration rate in type 2 diabetes. Issue 1 (December 2018) - Kamei, Nozomu; Yamashita, Mami; Nishizaki, Yuji; Yanagisawa, Naotake; Nojiri, Shuko; Tanaka, Kanako; Yamashita, Yoshinori; Shibata, Terumi; Murakoshi, Maki; Suzuki, Yusuke; Gohda, Tomohito
Abstract Chronic inflammation plays a crucial role in the development/progression of diabetic kidney disease. The involvement of tumor necrosis factor (TNF)-related biomarkers [TNFα, progranulin (PGRN), TNF receptors (TNFR1 and TNFR2)] and uric acid (UA) in renal function decline was investigated in patients with type 2 diabetes (T2D). Serum TNF-related biomarkers and UA levels were measured in 594 Japanese patients with T2D and an eGFR ≥30 mL/min/1.73 m2 . Four TNF-related biomarkers and UA were negatively associated with estimated glomerular filtration rate (eGFR). In a logistic multivariate model, each TNF-related biomarker and UA was associated with lower eGFR (eGFR <60mL /min/1.73 m2 ) after adjustment for relevant covariates (basic model). Furthermore, UA and TNF-related biomarkers other than PGRN added a significant benefit for the risk factors of lower eGFR when measured together with a basic model (UA, ΔAUC, 0.049, p < 0.001; TNFα, ΔAUC, 0.022, p = 0.007; TNFR1, ΔAUC, 0.064, p < 0.001; TNFR2, ΔAUC, 0.052, p < 0.001) in receiver operating characteristic curve analysis. TNFR ligands were associated with lower eGFR, but the associations were not as strong as those with TNFRs or UA in patients with T2D and an eGFR ≥30 mL/min/1.73 m2 .